Soiltesting formula fertilization with organic fertilizer addition for target yield cannot stand long due to stem lodging of rice - Zhao, Fucheng; Li, Fan; Zhou, Juan; Sun, Xiaolin; Wang, Yun; Jing, Liquan; Hou, Junfeng; Bao, Fei; Wang, Guiyue; Chen, Bin (Frontiers in Plant Science, 2022)
Soil testing formula fertilization using organic fertilizer (STFFOF)could increase grain yields and protect the ecological environment but the potential risks of STFFOF remains unclear. In order to assess the risk on rice stem lodging, a STFFOF field experiment is conducted continuously for 11 years. After 11 years of continuous STFFOF treatment, the stem lodging rate of rice substantially increases by 81.1%*, which completely overweigh its increase in yield. Further research found that STFFOF greatly decreases the concentration of Ca, SiO2, K, Mg, and non-structural carbohydrates in basal internodes, dramatically increases that of N, P, and weight per ear, but slightly affects the structural carbohydrates. The strong correlations imply the increasement in weight per ear, N, and P concentrations, and the significant decrease in starch in the basal internodes might directly increase the brittleness of stem internodes and further cause severe stem lodging and yield loss of rice. Results suggest that the potential risks of rice production including stem lodging must be considered when adopting the excessive exploration mode of productivity technology of paddy fields.